Green alternative methods for pretreatment of whole jujube before the drying process. (11th August 2021) - Bao, Tao; Hao, Xin; Shishir, Mohammad Rezaul Islam; Karim, Naymul; Chen, Wei
Abstract: BACKGROUND: Jujube contains a waxy cuticle that acts as a barrier against fungal pathogens, prevents nutrition damage and leakage due to mechanical damage, and maintains water content. Chemical treatment before drying is the most commonly used method for whole jujube. Although chemical pretreatment can effectively enhance drying kinetics, it can lead to the loss of soluble nutrients and cause food safety issues due to chemical residues. Therefore, this study aimed to explore the effect of various pretreatments (cold plasma, cold plasma activated water, ultrasonics, thermosonication, and blanching) on the drying process and quality properties of whole jujube so as to find effective green alternatives to chemical pretreatment. RESULTS: The application of chemical, cold plasma, and thermosonication significantly altered the surface morphology of jujube by etching larger cracks and holes, which can facilitate the transfer of moisture, thereby improving the drying rate and the effective diffusivity. Chemical, cold plasma, and thermosonication pretreatment reduced drying time by 18%, 12%, and 7% respectively, thereby increasing the content of total phenolics by 13%, 12%, and 6% respectively, and enhancing antioxidant capacity (ferric reducing antioxidant power) by 13%, 11%, and 3% respectively. In addition, chemical and cold plasma pretreatment reduced the generation of 5‐hydroxymethylfurfural by 25% and 15% respectively. CONCLUSION: Cold plasma is a promising green alternative method to chemical pretreatment for drying processes of whole jujube. © 2021 Society of Chemical Industry.